Peranan Perpustakaan Sekolah dalam Meningkatkatkan Minat Baca Siswa - Adibah Adibah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to describe the role of School Libraries in increasing students 'reading interest and what are the supporting and inhibiting factors in increasing students' reading interest. This research is a library research, taking the background of the role of the School Library in increasing students' reading interest. Data collection is carried out through several literature related to the subject matter. Data analysis was carried out by examining all data obtained then in croschek with other data data in a qualitative descriptive manner. The results of the study show that the role of the library is primarily to provide information from various sciences and disciplines. Therefore the role of the library is very central in increasing students' reading interest.